The uniqueness of bats as natural host of viruses and their implication to global health - Ronald Tarigan (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Bats are the natural host of several highly pathogenic viruses for human, such as SARS-CoV, Marburg, rabies, Hendra, Nipah, and ebola viruses. Bats did not show any clinical symptoms after infection with those highly pathogenic viruses. In addition, excessive inflammation and viremia were not developed in bats after viral infection. The absence of excessive inflammation is the compensation of their evolution as the only flying mammals. Their flight evolution also drives several unique features in their immune response that enable them to control the viral infection. This article summarizes current understandings about the uniqueness of bats as viral reservoir, the viral diversity in bats, the viral spillover from bats to human, and how to prevent the pandemic caused by emerging bat-borne viral zoonoses in the future. The understanding of how the antiviral response in bats work may provide valuable insights to control viral infection in human and domestic animals.